Analysis of Kink Reduction in SOI MOSFET Using Selective Back Oxide Structure - M. Narayanan; H. Al-Nashash; Baquer Mazhari; Dipankar Pal; Mahesh Chandra (Active and Passive Electronic Components)
This paper presents a complete analysis of the kink effect in SOI MOSFET and proposes a method for eliminating kink effect observed in the current-voltage output characteristics of a partially depleted SOI MOSFET device. In this method, back oxide for the device is introduced at selected regions below the source and drain and not continuously as in an SOI device giving rise to what is termed a “SELBOX” structure. Selective back oxide structure with different gap lengths and thicknesses was studied. Results obtained through numerical simulations indicate that the proposed structure can significantly reduce the kink while still preserving major advantages offered by conventional SOI structure. Although the new structure is capable of eliminating kink, for narrow gaps the device may still exhibit some kink effect. A device model that explains the kink behavior of the structure for varying gap lengths is also developed.